HUBUNGAN KETEPATAN WAKTU PEMBERIAN ANTIBIOTIK PROFILAKSIS PRE OPERASI DENGAN KEJADIAN INFEKSI LUKA OPERASI BEDAH UMUM - Hemiati, Nur; Kusyairi, Achmad; Hartono, Dodik (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2024)
Prophylactic antibiotics are antimicrobials used to prevent infection. Antibiotics are given 30 to 60 minutes before the skin incision. Incidence of surgical wound infection can be prevented by administering prophylactic antibiotics appropriately. However, in practice there is often a delay in the time of administration. This study aims to determine the relationship of timely administration of preoperative prophylactic antibiotics with the incidence of general surgical wound infections in Pasirian General Hospital. The research design used in this study was analytic observational with a retrospective approach. The sampling technique used was accidental sampling. Data were taken from pre- and post-surgery patients at the Pasirian General Hospital with the instrument used being an observation sheet. The sample studied were 34 respondents. The results of this study indicate that the timeliness of giving prophylactic antibiotics was mostly in the right category for 21 respondents (61.7%) while the occurrence of infection was mostly in the category of no infection for 19 respondents (55.9%). Based on the Chis Quare test, a p value of 0.002 ˂ α (0.05), that there is a relationship between the timeliness of giving preoperative prophylactic antibiotics and the incidence of general surgical wound infections at Pasirian General Hospital. By giving prophylactic antibiotics on time, it is hoped that during the operation, the antibiotics in the target tissue will reach optimal levels to inhibit bacterial growth so that surgical wound infections do not occur.